THE INFLUENCE OF COMPENSATION, MOTIVATION, WORK ENVIRONMENT, AND WORK DISCIPLINE ON JOB SATISFACTION - Rutinaias Haholongan; Elviayuliana Elviayuliana (Bajang Institute, 2022)
This study aims to understand the effect of compensation, motivation, work environment and work discipline on job satisfaction in home and personal care companies. The method used in this research is survey research. The population in this study is all working people. The samples in this study were 78 respondents. The data analysis method used is statistical analysis of descriptive data and analysis of respondents' answers. Statistical analysis methods can be selected and adapted to the research objectives. Calculations using the SPSS program version 25.00 with the coefficient of determination and hypothesis testing (t test). The results of the t test show that the compensation variable has no effect on job satisfaction. Motivational variables affect job satisfaction. Work environment variables affect job satisfaction. The work discipline variable influences job satisfaction.